IMPLEMENTATION OF BREAST CARE PRACTICE ASSISTANCE IN AN EFFORT TO INCREASE MILK PRODUCTION - Novi Nur Ratnasari; Sri Sumarni; Eka Apriadi F (Wealth Community Empowerment, 2024)
Postpartum mothers often experience problems with expressing breast milk. In 2020, Indonesia was actually still low, namely (66.1%) and increased to (69.7%) in 2021. The province of Central Java itself had an exclusive breastfeeding coverage rate lower than the national achievement figure, namely 64.19%. This community service aims to accompany postpartum mothers who have babies in their efforts to increase the smooth production of breast milk at the Karangpandan Community Health Center, Karanganyar Regency. This type of community service is the implementation of breastfeeding practice assistance. The target for this community service is secondary data, namely data on exclusive breastfeeding from August to September 2023 at the Karangpandan Community Health Center. The total sample involved 50 people, using a technique for all mothers with babies which was carried out for 6 weeks. Bivariate analysis used the Chi-Square test and Fisher's Exact Test. The results of the bivariate test showed that there was an influence between breast care assistance (p=0.001) and an increase in the smoothness of breast milk production.It can be concluded that assistance in breast care can increase breast milk production.